KRISIS PAHAM KENEGARAAN : TANTANGAN ETIKA HAK DAN KEWAJIBAN DALAM KONSTITUSI INDONESIA - E. Armada Riyanto (Litbang STFT Widya Sasana Malang, 2003)
One of the crucial problems of politics presently coped by Indonesia is crisis of the concept of the state. Scrutinizing the 1945 Constitution, the state of free Indonesia refers to the integralistic staatidee. It was Supomo’s opinion. The integralistic state is a kind of crystallisation of the implementation of asas kekeluargaan (family principle), the principle which is commonly regarded as being appropriate to the genuine Indonesian culture. Marsillam Simanjuntak wrote a book (Pandangan Negara Integralistik. Sumber, Unsur, dan Riwayatnya dalam Persiapan UUD 1945) criticizing Supomo’s integralistic staatidee. Marsillam’s opinion would provoke amendment of the 1945 Constitution in such a way that the idea of the free Indonesia built by the Founding Fathers is not clear anymore. In this article, first of all, I would like to discuss carefully Marsillam’s theses concerning such staatidee, conceiving that Supomo’s idea was based more on his belief of the asas kekeluargaan, an idea most appropriate to the nation of Indonesia rather than Hegel’s philosophy or German NAZI ideology. After this, I analyse the issue of federalistic state based on the first discussions of the Founding Fathers of Indonesia. Lastly, the article deals with the current debate on right and obligation of religion in the 1945 Constitution.